Effect of 5% Binahong (Anredera cordifolia) Leaf Extract in Lymphocyte Amount at The Tooth Extraction Wound Healing Process of Wistar Rat - Sugiharto, Tamara Al Kautsar; Ningsih, Juwita Raditya; Murdiyanto, Dendy; Hafizi, Ikmal (Universitas Muhammadiyah Surakarta, 2023)
Introduction: The growth of lymphocyte cells is one indication that the wound is healing. Binahong leaves contain flavonoids, saponins, tannins, terpenoids, and oleanolic acid that influence lymphocyte activity. This study aims to analyze the effect of a 5% gel made from binahong leaf extract on the number of lymphocytes throughout the healing process of wounds post tooth extraction. Methods: This research type is pure experimental research with a posttest-only control group design with ethical approval from Dr. Moewardi Hospital Number 1.847/X/HREC/2023. The research subjects were 36 mice divided into negative, positive, and treatment control groups. The number of lymphocytes was counted using a microscope with a magnification of 1000 times. Results: The results showed a significant difference in the number of lymphocyte cells between groups (p < 0.05) on days 5, 7, and 14. LSD results showed a significant difference (p < 0.05) between the treatment group and the negative control (day 2). -5, 7, and 14) with positive control (day 5). Conclusion: Shift in the peak number of lymphocytes in the treatment group compared to the negative and positive control groups. After tooth extraction, the amount of lymphocyte cells in the wound healing process is impacted by 5% binahong leaf extract gel.